Perfectionism and Eating Behavior in the COVID-19 Pandemic - Vacca, Mariacarolina; De Maria, Alessandra; Mallia, Luca; Lombardo, Caterina (Frontiers in Psychology, 2021)
The novel coronavirus disease 2019 (COVID-19) represents a massive global health crisis leading to different reactions in people. Those reactions may be adaptive or not depending on situational or psychological processes. Disordered eating attitudes and behaviours are likely to be exacerbated by the pandemic through multiple pathways as suggested by Rodgers and coll. (2020). Among the psychological variables that may have increased dysfunctional eating attitudes and behaviors as a consequence of the social distancing and isolation, we looked at perfectionism. Perfectionism is a well-recognized risk and maintaining factor of eating-related symptoms and interact with stress increasing the probability of dysfunctional reactions (e.g. Wang & Li, 2017). The present study investigated the relationship between multidimensional perfectionism and eating behaviors by considering the mediating role of psychological distress. Data were collected from two countries (Italy and Spain) by means of an online survey. The samples included 465 (63,4% female) participants from Italy and 352 (68,5% female) from Spain. Participants completed the short form of the Hewitt and Flett Multidimensional Perfectionism Scale (Lombardo, Novara, Mallia, Pastore, & Vacca, submitted) to assess self-oriented, other-oriented and socially-prescribed perfectionism, as well as the short form of Three Factors Eating Questionnaire (Karlsson, Persson, Sjöström, & Sullivan, 2000) and the and the Italian version of Depression Anxiety and Stress Scale-21 (Bottesi et al., 2015), respectively used to assess restrictive, emotional and uncontrolled eating on one hand, and depression, anxiety and stress on the other. Multigroup analysis was performed to test the hypothesized model. Results showed that other-oriented and socially prescribed perfectionism were indirectly related to most of the dysfunctional eating aspects through the mediation of psychological distress, and the pattern obtained was consistent in both countries. These findings evidence that the psychological distress potentially related to the COVID-19 disease mediates the negative impact of interpersonal perfectionism and the tendency to eat in response to negative emotions.